Protective Effects of Kolaviron against Phenylhydrazine-Induced Hepatotoxicity, Genotoxicity, and Splenic Pathology in Wistar Rats (Nigerian Journal of Physiological Sciences, 2025)
Phenylhydrazine (PHZ) triggers oxidative stress through the generation of reactive oxygen species and lipid peroxidation, resulting in organ and DNA damage. Kolaviron (KV), a biflavonoid complex extracted from Garcinia kola seeds, has shown properties that combat oxidative stress and protect cells. Aim was to evaluate the protective effects of kolaviron against phenylhydrazine-induced hepatotoxicity, splenic pathology, and genotoxicity in Wistar rats. Twenty-eight male rats were divided into four groups: Control (distilled water), PHZ (40 mg/kg intraperitoneally for 3 days), PHZ+KV (PHZ at 40 mg/kg+KV at 100 mg/kg orally for 14 days), and KV alone (100 mg/kg orally for 14 days). Hepatotoxicity, splenic pathology, and genotoxicity were assessed via biochemical analyses, oxidative stress markers, antioxidant parameters, histopathology, and micronucleus testing in bone marrow cells. Results showed PHZ significantly elevated liver enzymes (p